PROBLEMS FACED BY A MEDICAL JOURNAL EDITOR A FAREWELL EDITORIAL - Badar, Ahmed (Journal of Ayub Medical College Abbottabad, 2006)
Voluntary editorship of a medical journal is a pleasure and is very enjoyable if you just ’˜sit’ on the board. It is very stressful if you decide to actively work. Managing Editor is an editor who is always under immense pressure. This ’˜different breed’ editor is a bridge between the ’˜elite’ members of the board, office staff, authors, reviewers, printers, subscribers, advertisers and well-wishers. All these eight integral pillars of a journal consult managing editor for all their worries, queries, problems and frustrations. Naturally it is the managing editor that is ’˜blamed’ for every bad thing, and is forgotten at the time of ’˜cheers’. But let me tell you, the only thing that keeps a managing editor ’˜going’ is the satisfaction of keeping a living thing alive. For me my journal was a living human being, a baby that I brought up and once brought up it started bringing me up. I have worked for JAMC from 1997 to 2006. In this period we managed to get the journal indexed in Index Medicus/Medline/Pubmed besides many other indexations. I have enjoyed working for JAMC in all these years and this journal has returned back to me more than the effort that I have actually put into it. I am leaving the editorship to let new persons come in to break monotony of 10 years. I agree with a medical journalism dictum that ’˜as the new persons take over, new ideas flow in and progress of a progressive journal becomes faster.’1 Here I will take an opportunity to highlight problems faced by a managing editor, keeping the pleasures for some other time. I have grouped problems faced by me in order of gravity of problem and arranged groups in order of importance. I will briefly discuss a few points that need explanation refraining from details. I am sure this document will help many persons who are planning to become editors or to bring out journals.